Perception of true linear self-motion using vestibular stimulation in humans : a mathametical electrophysiological analysis - Nolan, Hugh (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2013)
In humans, the percept of motion is a combination ol multiple sensors modalities, primarily involving vestibular, visual and somatosensory (Ohmi, 1996). The ability to properly perceive motion enables us to function normally within society; conversely, impaired motion processing puts people at risk of falls and injury (Warren et al., 1989). The integration of vestibular information happens at multiple hierarchical levels from brainstem to cortex. Our understanding of the neural substrates which underlie vestibular processing and motion perception is limited (Blanke and Lopez 2010). Multisensory integration is known to be inefficient in fallers (Setti et. al, 2011) while vestibular organs degrade and produce less reliable information, inducing compensatory mechanisms whicb rely on multisensory integration (Pfaltz., 1983; .Sadeghi et al., 2011). Pbe interaction between ageing and processing of vestibular information is not straightforward or fully understood.
Keywords: Electronic & Electrical Engineering, Ph.D.; Ph.D. Trinity College Dublin.